2005
DOI: 10.1063/1.1847728
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nitrogen chemical states in N-doped ZnO via x-ray photoelectron spectroscopy

Abstract: Nitrogen-doped films of ZnO grown by two methods, metalorganic chemical vapor deposition (MOCVD) and reactive sputtering, were studied with x-ray and ultraviolet photoelectron spectroscopy (XPS and UPS). Systematic differences in the N chemical states were observed between films grown by sputtering and MOCVD: only two N chemical states were observed in films grown by reactive sputtering, whereas four N chemical states were observed in MOCVD films. To aid in the assignment of the N chemical states, photoemissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
148
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(161 citation statements)
references
References 36 publications
13
148
0
Order By: Relevance
“…Furthermore, the Ga 2 O 3 source provides more oxygen during the sputtering process [11], leading to decreased oxygen vacancies and enhanced crystallinity. A similar effect of the Ga oxide source on ZnO crystallinity has also been reported by other groups [26]. The crystallite size of Ga-N co-doped ZnO films deposited at a substrate temperature of 300 and 500°C is 35 and 24 nm, respectively, indicating that more N is incorporated in these films.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, the Ga 2 O 3 source provides more oxygen during the sputtering process [11], leading to decreased oxygen vacancies and enhanced crystallinity. A similar effect of the Ga oxide source on ZnO crystallinity has also been reported by other groups [26]. The crystallite size of Ga-N co-doped ZnO films deposited at a substrate temperature of 300 and 500°C is 35 and 24 nm, respectively, indicating that more N is incorporated in these films.…”
Section: Methodssupporting
confidence: 63%
“…Argon ion sputtering (3 keV, 0.8 lAmm -2 , 120 s) was used to clean samples prior to analysis. Other aspects of the photoemission system are described in detail elsewhere [26].…”
Section: Methodsmentioning
confidence: 99%
“…From Fig.8, we can see that one peak located at 400.02 ±0.3 eV can be observed in both samples. It is known that the N 1s peak from molecularly adsorbed NH 3 on metal and semiconductor surfaces appears at 400-401 eV, whereas for the partially decomposed species, i.e., NH x (x= 1, 2), N 1s peak appears at 398-399.4 eV [52][53][54]. Thus, the peak at 400.02…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] However, studies have since shown that N-doping compensates p-type behaviour by forming shallow donors rather than acceptors, consequently p-type ZnO is unlikely to form. [21][22][23][24][25] Point defects situated deep in the ZnO bandgap (E g ) give rise to photoluminescence (PL) referred to as deep-level emission (DLE) observed under excitation >E g . This DLE emission has been employed in visible light-emitting diodes 26,27 and photodetectors.…”
Section: Introductionmentioning
confidence: 99%